Proceedings (90) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Lethal yellowing-like diseases of coconut is the proceedings of a workshop held in November 1995 in Elmina, Ghana edited by S J Eden-Green and F Ofori 1997 308ppprice UKL35.00 ISBN 0 85954 488 5Natural Resources Institute, The University of...